The Phenomenon of Korean Pop Culture among Students of Universitas Satya Negara Indonesia (Oratio Directa, 2019)
Korean pop culture has been openly received by Indonesian youth and is popular among students of Universitas Satya Negara Indonesia (USNI). This study aims to explain how USNI students experience and interpret Korean pop culture and the lifestyle changes associated with it. The study employs a descriptive qualitative approach using Edmund Husserl's phenomenological method. Data were collected through observation, interviews, questionnaires, and documentation, then interpreted through the participants' conscious experiences. The findings show that Korean pop culture introduces a new form of popular culture to USNI students. Interest in Korean music, fashion, food, language, and idols encourages changes in preferences and lifestyles. Peer environments and social media are important channels for introducing and reinforcing this interest.
Keywords: Popular culture; Korean pop; Phenomenology; Lifestyle; USNI students